Recent progress on biomass‐derived ecomaterials toward advanced rechargeable lithium batteries - Liu, Jia; Yuan, Hong; Tao, Xinyong; Liang, Yeru; Yang, Seung Jae; Huang, Jia‐Qi; Yuan, Tong‐Qi; Titirici, Maria‐Magdalena; Zhang, Qiang (EcoMat (Beijing, China), 2020)
Biomass materials are of great interest in high‐energy rechargeable batteries due to their appealing merits of sustainability, environmental benefits, and more importantly, structural/compositional versatilities, abundant functional groups and many other unique physicochemical properties. In this perspective, we provide both overview and prospect on the contributions of biomass‐derived ecomaterials to battery component engineering including binders, separators, polymer electrolytes, electrode hosts, and functional interlayers, and so forth toward high‐stable lithium–ion batteries, lithium–sulfur batteries, lithium–oxygen batteries, and solid state lithium metal batteries. Furthermore, based on the multifunctionalities of bio‐based materials, the design protocols for battery components with desired properties are highlighted. This perspective affords fresh inspiration on the rational designs of biomass‐based materials for advanced lithium‐based batteries, as well as the sustainable development of advanced energy storage devices. Biomass Derived EcoMaterials with special properties and functionalities render great promise in advanced rechargeable lithium batteries. We summarize the recent progresses of bio‐based ecomaterials in addressing critical problems in lithium battery systems, and offer some perspectives for promoting the greenness and sustainability of energy devices.